Mn-containing bioceramics inhibit osteoclastogenesis and promote osteoporotic bone regeneration via scavenging ROS - Li, Jianmei (Bioact Mater, 2021)
Osteoporosis is caused by an osteoclast activation mechanism. People suffering from osteoporosis are prone to bone defects. Increasing evidence indicates that scavenging reactive oxygen species (ROS) can inhibit receptor activator of nuclear factor κB ligand (RANKL)-induced osteoclastogenesis and suppress ovariectomy-induced osteoporosis. It is critical to develop biomaterials with antioxidant properties to modulate osteoclast activity for treating osteoporotic bone defects. Previous studies have shown that manganese (Mn) can improve bone regeneration, and Mn supplementation may treat osteoporosis. However, the effect of Mn on osteoclasts and the role of Mn in osteoporotic bone defects remain unclear. In present research, a model bioceramic, Mn-contained β-tricalcium phosphate (Mn-TCP) was prepared by introducing Mn into β-TCP. The introduction of Mn into β-TCP significantly improved the scavenging of oxygen radicals and nitrogen radicals, demonstrating that Mn-TCP bioceramics might have antioxidant properties. The in vitro and in vivo findings revealed that Mn(2+) ions released from Mn-TCP bioceramics could distinctly inhibit the formation and function of osteoclasts, promote the differentiation of osteoblasts, and accelerate bone regeneration under osteoporotic conditions in vivo. Mechanistically, Mn-TCP bioceramics inhibited osteoclastogenesis and promoted the regeneration of osteoporotic bone defects by scavenging ROS via Nrf2 activation. These results suggest that Mn-containing bioceramics with osteoconductivity, ROS scavenging and bone resorption inhibition abilities may be an ideal biomaterial for the treatment of osteoporotic bone defect.